Effect of Clearfelling and Reforestation on Runoff and Peak Rates in Small Watersheds - Mathur, R. N.; Babu, Ram; Joshie, P.; Singh, Bakhshish (Indian Forester, 1976)
Two small forest (brush) Watersheds W1F (1.45 ha) and W2F (0.87 ha) were calibrated for 8 years (1961-68). During calibration period W1F gave 18% more runoff and 63% higher peak rate of runoff as compared to W2F. In the year 1969, W1F was clearfelled and reafforested with Eucalyptus species. The post calibration relationship indicates that W1F (treated) after afforestation gave 10% less runoff and peak rates of runoff as compared to W2F (untreated). The total reduction of 28% in runoff and 73% in peak rate is due to afforestation resulting in fully stocked plantation and a dense undergrowth. The study has quantitatively indicated the effectiveness of afforestation for flood control purposes by reducing runoff (28%) and of drastically reducing the peak rate of runoff (73%).